2019
DOI: 10.1002/eat.23157
|View full text |Cite
|
Sign up to set email alerts
|

Impaired brain endocannabinoid tone in the activity‐based model of anorexia nervosa

Abstract: Objective Despite the growing knowledge on the functional relationship between an altered endocannabinoid (eCB) system and development of anorexia nervosa (AN), to date no studies have investigated the central eCB tone in the activity‐based anorexia (ABA) model that reproduces key aspects of human AN. Method We measured levels of two major eCBs, anandamide (AEA) and 2‐arachidonoylglycerol (2‐AG), those of two eCB‐related lipids, oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), and the cannabinoid type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 84 publications
4
18
0
Order By: Relevance
“…Overall, the reduction of Cnr1 expression in the Hyp might be a partial loss of need to restore energy homeostasis, whereas the down‐regulation in the NAc could be linked to anhedonia, which might occur during the development of the phenotype. In our previous mentioned paper (Collu et al, 2019) with regard to CB1 receptors, we found a significantly decreased receptor density in the lateral Hyp and in the dental gyrus of the hippocampus of ABA rats while only a trend in the PFC.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Overall, the reduction of Cnr1 expression in the Hyp might be a partial loss of need to restore energy homeostasis, whereas the down‐regulation in the NAc could be linked to anhedonia, which might occur during the development of the phenotype. In our previous mentioned paper (Collu et al, 2019) with regard to CB1 receptors, we found a significantly decreased receptor density in the lateral Hyp and in the dental gyrus of the hippocampus of ABA rats while only a trend in the PFC.…”
Section: Discussionsupporting
confidence: 53%
“…Very recently, we have found 2‐AG levels significantly decreased in several brain area of ABA rats after the induction phase (Collu et al, 2019), this reduction of the eCB tone could be responsible for the development of altered feeding behaviors (Wu, Clark, & Palmiter, 2012) and cognitive and emotional alterations (Nestler & Carlezon Jr., 2006), all hallmarks in AN (Koch, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…2-AG significantly decreased in various brain areas but not in the caudate putamen, whereas no changes were observed in AEA. Density of CB1r was reduced in the dentate gyrus of Hipp and in the lateral Hyp (369). These results suggested that ECS is involved in the contribution and maintenance of some aspects in the pathophysiology of AN.…”
Section: Animal Studiesmentioning
confidence: 71%
“…In the past 15 years, the endocannabinoid system (ECS) has appeared as a lipid signaling system involved in the energy balance regulation, as it has control on every aspect of calorie regulation [6]. This system consists of endogenous ligands N-arachidonoylethanolamide (anandamide), 2-arachidonoyl glycerol (2 AG), the cannabinoid 1 and 2 receptors, and enzymes responsible for the biosynthesis and degradation of ligands [7]. The endogenous ligands are lipid derivatives of a ω 6polyunsaturated fatty acid, arachidonic acid (ARA), with multiple functions [8].…”
Section: Introductionmentioning
confidence: 99%